Transcutaneous auricular vagus nerve stimulation as a potential therapy for attention deficit hyperactivity disorder: modulation of the noradrenergic pathway in the prefrontal lobe - Zhi, Jincao; Zhang, Shiwen; Huang, Meiling; Qin, Huan; Xu, He; Chang, Qing; Wang, Yan (Frontiers in Neuroscience, 2024)
Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by developmental impairments, inattention, motor hyperactivity, and impulsivity. Currently, there is no effective intervention that can completely cure it. One of the pathogenic mechanisms of ADHD involves abnormalities in the norepinephrine (NE) pathway within the prefrontal cortex (PFC). In recent years, transcutaneous auricular vagus nerve stimulation (taVNS), a non-invasive neuromodulation technique, has demonstrated promising potential in the treatment of neurological and psychiatric disorders. However, its application in the management of ADHD remains relatively unexplored. Previous studies have shown that taVNS exerts therapeutic effects on attention, cognition, arousal, perception, and behavioral regulation primarily through activating the vagus nerve conduction pathway, specifically targeting the nucleus tractus solitarius - locus coeruleus - NE pathway. These findings have led to the hypothesis that taVNS may be an effective intervention for ADHD, with NE and its pathway playing a pivotal role in this context. Therefore, this review comprehensively examines the correlation between NE pathway alterations in the PFC and ADHD, the mechanism of action of taVNS, and the potential role of the NE pathway in treating ADHD with taVNS, aiming to provide a theoretical foundation for clinical applications.